Diagnostic accuracy of Centor score for diagnosis of group a Streptococcal pharyngitis among adults in primary care clinics in Malaysia - Muthanna, AbdulRahman; Shamsuddin, Nurainul Hana; Abdul Rashid, Aneesa; Shariff Ghazali, Sazlina; Awang Hamat, Rukman; Maliza Mawardi, Maliza Mawardi; Salim, Hani Syahida; Zakariah, Siti Zulaikha (Penerbit Universiti Sains Malaysia, 2022)
Background: Pharyngitis is a common presentation seen in general practice, but it is difficult to differentiate whether its etiology is viral or bacterial. The Centor score gives an approximation of the etiology of the pharyngitis, which informs physicians of the need to prescribe antibiotics. This study aimed to assess the validity of the Centor score in diagnosing Group A streptococcal (GAS) pharyngitis amongst adults in Malaysia. Methods: This cross-sectional study was conducted to compare the clinical criteria of the Centor score to the gold standard throat swab culture results amongst 215 adults presenting with sore throat in primary care clinics. The participants were adult patients who complained of sore throat and visited the three public primary care clinics in Sepang, Malaysia. The convenience sampling method was used. The throat swabs were analysed for β-haemolytic streptococci. Demographic and clinical data, including the Centor score, were analysed in relation to the pathogen. Results: Pharyngitis was diagnosed in 130 (60.5%) of the participants. Six isolates (2.4%) were identified as GAS pharyngitis. Both Centor scores 3 and 4 had a sensitivity of 50%, and specificities of 97.6% and 100%, respectively. Conclusion: A Centor score < 3 is favourable for excluding a diagnosis of GAS pharyngitis. Centor scores 3 and 4 require further examination to confirm a diagnosis of GAS pharyngitis.